2020
DOI: 10.3390/foods9010050
|View full text |Cite
|
Sign up to set email alerts
|

Acacia Gum as a Natural Anti-Plasticizer for the Production of Date Syrup Powder: Sorption Isotherms, Physicochemical Properties, and Data Modeling

Abstract: The thermoplastic and hygroscopic behaviors of date syrup (DS) challenge the DS drying process. In this context, DS was mixed with 30%, 40%, 50%, and 60% acacia gum (AG) and subjected to a drum dryer. The chemical composition, bulk density (pb), caking degree (CD), glass transition temperature (Tg), and color values of DS powders were studied. The sorption isotherms were also obtained and compared to that of those predicted by mathematical models. According to the results, increasing the AG concentration enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…Where, GCSF was scored statistically the lowest amount of moisture (4.64 ± 1.81 g/100g). In harmony, Mansoori et al (2020) reported that Arabic gum was recorded 9.17 ± 0.19 % of moisture. Parallel, Adeyeye (2016) mentioned that sorghum flour moisture content was 10.28 ± 0.39.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Where, GCSF was scored statistically the lowest amount of moisture (4.64 ± 1.81 g/100g). In harmony, Mansoori et al (2020) reported that Arabic gum was recorded 9.17 ± 0.19 % of moisture. Parallel, Adeyeye (2016) mentioned that sorghum flour moisture content was 10.28 ± 0.39.…”
Section: Resultsmentioning
confidence: 94%
“…Whereas, Adeyeye (2016) reported that sorghum flour was scored 10.72 ± 0.24 % of crude protein. Also, Mansoori et al (2020) exhibited that Arabic gum was scored 2.50 ± 1.07 % of crude protein. In terms of moisture, results stated that Arabic gum was observed statistically the highest amount of moisture (12.23 ± 0.86 g/100g) among all samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The statistical evaluation of models was performed using the root mean square error (RMSE), chi‐square ( x 2 ), and determination coefficient ( R 2 ) (Mansoori, Majzoobi, Gavahian, Badii, & Farahnaky, 2020). The best conformity of experimental data was validated on statistics parameters such as RMSE and x 2 , which represent the rate of deviation square of experimental values with predicted values by mathematical models.…”
Section: Methodsmentioning
confidence: 99%